MEDICAL PERSONNEL AS THE KEY TO SOCIALLY RESPONSIBLE GREEN TRANSITION IN THE HEALTHCARE SECTOR - Zariņš, Kristaps; Siders, Emīls Georgs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
To implement the socially responsible green transition in the Healthcare sector, it is essential to involve competent and educated personnel/staff. Article 48 of the Medical Treatment Law (Ārstniecības likums) of the Republic of Latvia stipulates that a medical practitioner has a duty to regularly improve his or her professional qualifications. Article 1 also defines improvement of professional qualifications as part of post-graduate education in a specific profession or specialty, which occurs in accordance with a freely selected education program, though the content and time of acquisition of which is not regulated. However, it must be noted that almost all programs offered by the Ministry of the Health of the Republic of Latvia for the improvement of practitioners’ professional qualifications refer to the acquisition of skills and knowledge necessary to improve the process of treating patients. Although various international and national regulatory acts determine the obligations of state institutions to include the green transition into their operations, the involvement of the institution’s employees is not discussed. This study aims to analyze and reflect on the competence of medical personnel and students regarding patient treatment and to analyze the compliance of the regulations of the Cabinet of Ministers with international and national regulations related to the creation of a socially responsible and sustainable state. UN Sustainable Development Goal Nr.4 “Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all” includes the necessity to ensure that all trainees acquire the knowledge and skill needed to promote sustainable development, including education regarding sustainable development and sustainable lifestyle. Within the scope of the research examples of positive foreign green transition practices will be evaluated. The results obtained within the framework of the research indicate the need to develop specific guidelines for the education of medical personnel, regarding the implementation of a socially responsible green transition in the healthcare sector, ensuring quality education in terms of promoting sustainable development.